1998
DOI: 10.1136/mp.51.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 and human neoplasia

Abstract: Neoplasia is characterised by abnormal regulation of the cell cycle. Cyclin D1 is a protein derived from the PRAD1, CCND1 or bcl-1 gene on chromosome 11q13, which is involved in both normal regulation of the cell cycle and neoplasia. In the G 1 (resting) phase of the cell cycle, cyclin D1 together with its cyclin dependent kinase (cdk) partner, is responsible for transition to the S (DNA synthesis) phase by phosphorylating the product of the retinoblastoma gene (pRB), which then releases transcription factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
213
0
9

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(229 citation statements)
references
References 113 publications
(57 reference statements)
4
213
0
9
Order By: Relevance
“…Cyclin D1 also exhibits CDK-independent activities that influence apoptotic pathways, cellular migration, and angiogenesis all of which may be important in the neoplastic context. [10][11][12]16 Over-expression of cyclin D1 has been documented in diverse neoplasms including breast carcinoma, head and neck squamous carcinoma, parathyroid adenoma and mantle cell lymphoma, and some studies have shown a correlation between increased cyclin D1 and adverse prognosis. Therefore, our observation that cyclin D1 immunoreactivity was usually lost in neoplastic endocervical lesions seemed to be a counter-intuitive finding, particularly as such lesions are known to show prominent mitotic activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclin D1 also exhibits CDK-independent activities that influence apoptotic pathways, cellular migration, and angiogenesis all of which may be important in the neoplastic context. [10][11][12]16 Over-expression of cyclin D1 has been documented in diverse neoplasms including breast carcinoma, head and neck squamous carcinoma, parathyroid adenoma and mantle cell lymphoma, and some studies have shown a correlation between increased cyclin D1 and adverse prognosis. Therefore, our observation that cyclin D1 immunoreactivity was usually lost in neoplastic endocervical lesions seemed to be a counter-intuitive finding, particularly as such lesions are known to show prominent mitotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Many tumors exhibit abnormalities within the RB-p16-cyclin D1 pathways, and often these lead to increased activity of cyclin D1. [10][11][12] However, we have noted in routine practice that adenocarcinoma in situ and invasive cervical adenocarcinoma usually lack expression of cyclin D1, whereas the nuclei of most normal endocervical epithelial cells are positively stained. This seems a surprising finding as neoplastic endocervical lesions are typically characterized by prominent mitotic activity and show increased expression of the proliferationassociated marker Ki-67/MIB-1.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The role of cyclin D1 in cancer cell growth has been well documented and reviewed (Donnellan and Chetty, 1998). Signals from growth factors and mitogens eventually activate AP-1, which in turn activates cyclin D1.…”
Section: Ap-1 Blockade Downregulates Cyclins and E2f1 Q Shen Et Almentioning
confidence: 99%
“…[11][12][13] While highly characteristic of MCL, elevated cyclin D1 protein has been demonstrated in other lymphoproliferative processes such as hairy cell leukemia, 11,14,15 plasma cell dyscrasias, 11,12 rare cases of B-cell CLL/SLL, 11,12 and epithelial malignancies. 16 Elevated cyclin D1 mRNA expression has been demonstrated by Northern blot 17,18 and in situ hybridization analyses in MCLs. 19 Similarly, RNA expression studies have also shown elevated levels of cyclin D1 transcripts in the majority of MCLs and in a minority of other lymphoproliferative disorders by conventional end-point reverse trancription-polymerase chain reaction (RT-PCR)-based analyses.…”
mentioning
confidence: 99%